Bidentate Schiff base coordinated square planer nickel(II) complexes: Synthesis, crystal structure, DFT/TD-DFT calculation and DNA/protein binding. (1st June 2021) - Patra, Apu; Puschmann, Horst; Manna, Subal Chandra
Graphical abstract: Two almost identical square planer complexes [Ni(L 1 )2 ] (1 ) and [Ni(L 2 )2 ] (2 ) [HL 1 = 2-[(2-methoxy-ethylimino)-methyl]-phenol; HL 2 = 2-methoxy-6-[(2-methoxy-ethylimino)-methyl]-phenol] have been synthesized and characterized through structure determination and DFT/TDDFT calculation. Spectroscopic studies and viscosity measurement evidence that the complexes interact with CT-DNA with intercalative binding mode, whereas interactions of complexes with albumin proteins occur through ground state association process. Abstract: Two mononuclear square planer Ni(II) complexes, [Ni(L 1 )2 ] (1 ) and [Ni(L 2 )2 ] (2 ) [HL 1 = 2-[(2-Methoxy-ethylimino)-methyl]-phenol; HL 2 = 2-Methoxy-6-[(2-methoxy-ethylimino)-methyl]-phenol] have been synthesized and characterized through X-ray single crystal structure determination and DFT/TDDFT calculation. Both the complexes crystallize with P21 /c space group. C-H…π interactions results 2D and 1D supramolecular network of complexes 1 and 2, respectively. Interaction of complexes with calf thymus DNA (CT-DNA), bovine serum albumin (BSA) and human serum albumin (HSA) were studied by using both UV–vis absorption and emission spectroscopic techniques, and the calculated values of intrinsic binding constants with CT-DNA are (1.43 ± 0.56) × 10 6 M −1 (for 1 ) and (1.25 ± 0.79) × 10 6 M −1 (for 2 ).